Corporate Tax Avoidance and Firm Risk: What Role Does Firm Performance Play? - Fatma Bougacha; Mouna Guedrib (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Can firm performance moderate the relationship between tax avoidance and firm risk in the French context? Motivation- Previous studies have investigated the impact of tax avoidance on corporate risk, yet consensus remains elusive. These discrepancies suggest that findings may be influenced by specific company characteristics, such as performance. Guedrib and Bougacha (2024) discovered a negative relationship between tax avoidance and corporate risk using annual tax avoidance as a measure. Our study adopts the approach of Dyreng et al. (2008) by examining a long-term measure to mitigate distortions arising from tax accrual effects and short-term fluctuations. Idea- This study seeks to evaluate the impact of tax avoidance on firm risk and investigate how firm performance might moderate this dynamic. Data- Our research examines 301 observations of French companies listed on the CAC 40 index. We analyze data from 2010 to 2022, collected from 2008, using DATASTREAM database. Tools- This research employs the feasible generalized least squares (FGLS) method. Firm performance is evaluated using both metrics, while tax avoidance is estimated using the long-run cash effective tax rate. Findings- The research indicates that firm performance plays a moderating role in how tax avoidance affects firm risk. Accounting performance coupled with tax avoidance typically decreases firm risk, whereas market performance combined with tax avoidance tends to increase it. Further analysis reaffirms these findings, particularly among firms exhibiting high tax risk. Contribution- This study underscores the importance for investors to consider both firm performance and tax avoidance as interconnected indicators to enhance decision-making processes.
Keywords: M41; M42; 650; Tax Avoidance; Firm risk; Firm performance; Long-run Cash ETR; CAC 40.